Fixed-bed Column Study for Adsorption of Cadmium on Oil Palm - Chai Ping Ling; Ivy Ai Wei Tan; Leonard Lik Pueh Lim (Journal of Applied Science & Process Engineering, 2016)
The spread of heavy metal pollution in the environment can lead to the contamination of crops and water for consumption. An approach to control the spread of groundwater pollution is by using a permeable reactive barrier with granular activated carbon. In this study, the adsorption of Cd(II) ions was conducted in a continuous flow fixed-bed column by using oil palm shell-derived activated carbon. The activated carbon column performance was evaluated by manipulating the activated carbon bed height, cadmium solution flow rate and influent concentration. The increase in bed height increased the amount of adsorbent used, thus increasing the total removal of Cd(II) and prolonged the lifespan of the activated carbon column. However, the increase in flow rate and influent concentration resulted in the shortened lifespan of the column. The column system with a bed height of 5.5 cm, flow rate of 2.0 mL/min and 200 mg/L influent concentration showed the best Cd(II) uptake performance in this study. The column performance were best fitted to the Thomas model and Yoon-Nelson model for the longest bed depth of 5.5 cm, all flow rates studied and highest influent concentration of 200 mg/L, with correlation coefficient greater than 0.95.